Análisis de fallas de los aisladores de porcelana de 13,8 kv aplicando técnica de ultrasonido acústico - Cruz Loya, Miguel Ángel (2023)
The main objective of the research project presented is to carry out an exhaustive analysis of the failures of porcelain insulators in electrical power systems at a level of 13.8 kV, in order to propose solutions to prevent interruptions in the supply of electrical energy; To achieve this, the acoustic ultrasound technique was used, which is a non-destructive tool; This technique is based on the emission of high-frequency sound waves that propagate through the insulator material; When these waves encounter an anomaly, such as the corona effect, tracking or electric arc, a refraction occurs that is recorded in a waveform as a function of time; This waveform can be analyzed using the Fourier Transform, which converts the waveform as a function of frequency; In this way, a specific stamp of each analyzed element is obtained that allows determining the type of anomaly present in the insulator; A bibliographic and field investigation was carried out to collect information on the types of failures such as corona effect, partial discharges (Tracking) and electric arc to evaluate the effectiveness of the acoustic ultrasound technique in their detection; The project is part of the research lines of the Technical University of Cotopaxi related to alternative and renewable energies, energy efficiency and environmental protection; It is expected that the research results will contribute to improving energy quality and avoiding interruptions in the electricity supply through diagnostic and preventive measures, improving the quality of service for end users.